Return to Earth! - O'Ryan, Ray (O'Ryan, Ray. Galaxy Zack, 2015)
"Zack is headed back to Earth for the first time since moving to Nebulon. He can't wait to see Bert and show his new friend, the former bully Seth Stevens, all around his old stomping grounds. When Zach's dog Luna escapes and goes missing, sightseeing plans take an unexpected turn. Will Zack find Luna before he has to head home to Nebulon?--